Kekuatan Hukum Informed Consent Dalam Praktek Euthanasia Di Indonesia - Atriani, Dewi; Yulianto, Ade Yusuf (Jurnal Risalah Hukum, 2023)
The existence of informed consent is a stronghold for doctors to act calmly after the permission of the patient or the patient's family, while euthanasia is defined as the act of "lethal injection" to patients who have suffered greatly with very little or no chance of recovery. The purpose of this research is to find out how the regulation of informed consent, euthanasia and the legal force of informed consent in protecting doctors who practice euthanasia in Indonesia. This research uses a normative method by examining library materials and laws regulating to resolve the legal issues. From this study, it is found that informed consent has been regulated in Law No. 17 of 2023 concerning Health, Minister of Health Regulation No. 290/MENKES/PER /III/2008 concerning Consent for Medical Actions and other regulations related to the approval of medical actions, while the regulation of euthanasia is only limited to active euthanasia in Article 461 of the Criminal Code. The legal force of informed consent cannot protect doctors in the practice of euthanasia in Indonesia, due to the non-fulfillment of the legal requirements of the agreement based on Article 1320 of the Civil Code and the absence of specific euthanasia regulations other than the provisions of active euthanasia which are included in criminal acts against life or murder.